Semiotic Perspective in Mathematics Problem-solving (Universitas Pendidikan Indonesia Kampus Cibiru, 2023)
Semiotics is simply defined as the use of signs to represent mathematical concepts in problem-solving. The semiotic process of mathematics is the process of forming meaning from signs of a triadic relationship between representamen/symbols (R), objects (O), and interpretants (I) in solving mathematical problems. The purpose of this study is to describe the stages of solving mathematical problems based on a semiotic perspective on the concept of linear equations. This research is a qualitative descriptive study through the stages of giving questions (problems), determining subjects, interviews, data analysis, and drawing conclusions. The subject of this research was one junior high school student in one of the schools in West Bandung. The results of the study show that students go through four steps in solving mathematical problems which allow the emergence of object signs, symbols, and interpretations. Students show object signs and symbols in all indicators, while interpretation only appears in several problem-solving steps. As a suggestion for further research, it is suggested to consider the use of other semiotic components in explaining mathematical thinking processes.